COMPRESSIONAL AND MECHANICAL PROPERTIES OF NATIVE AND MODIFIED STARCHES OF Solenostemon rotundifolius COMPARED WITH GELATIN AND Zea mays - A,.R, ODUOLA; .H, MUSA; ,T.S, ALLAGH; ,O.J, ADAMU; ,I.V, EMENIKE (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The aim of this study is to determine the compressional and mechanical properties of native and modified starches of Solenostemon rotundifolius compared with gelatin and Zea mays. 500 mg compacts of Solenostemon rotundifolius starch (SRS), Water – prepared pregelatinised starch (PGSW), Alcohol – dehydrated pregelatinised starch (PGSA), Gelatin (GLT) and Maize starch (MZS) were made using a hydraulic press at various tableting pressures (56.6-169.9MNm-2) and investigated for deformation characteristics and tensile strength. The ability of a powder bed to be compressed and consequently be reduced in volume is referred to as compression, which depends on the mechanical strength of the material. It plays an important role in the manufacturing of tablets. The ranking order for mean yield pressure, PY was PGSA>MZS>GLT>SRS>PGSW; total plastic deformation, DA, was SRS<GLT<PGSW<MZS<PGSA showing that SRS and PGSW deforms plastically with fast onset of deformation while PGSA has tendency to show fragmentation before plastic deformation. The tensile strength results for SRS (0.22-0.70MNm-2), PGSW (0.29-0.79MNm-2), PGSA (1.76-1.82MNm-2) and MZS (0.71-1.50-1.44MNm-2) which were in agreement with compression studies showed that SRS and the modified starches produced harder and more compact tablets compared with Maize starch B.P. Hence, SRS, PGSW and PGSA could be useful in formulation of tablets with desired mechanical properties.